Traditional industry in the economy of colonial India - Roy, Tirthankar (Cambridge studies in Indian history and society, 1999)
Tirthankar Roy challenges the view that traditional industry was destroyed in the colonial period. Roy argues that while traditional industry did evolve during the industrial revolution, these transformations had a galvanizing effect on manufacturing generally and that the major industries in post-independence India were shaped by such transformations.